2011
DOI: 10.1093/bja/aeq403
|View full text |Cite
|
Sign up to set email alerts
|

h-indices in a university department of anaesthesia: an evaluation of their feasibility, reliability, and validity as an assessment of academic performance

Abstract: Agreement between the two databases was problematic. There was evidence of construct validity; however, the overlap between academic ranks limits the discriminative power of a low h-index.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
45
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 17 publications
5
45
0
1
Order By: Relevance
“…Output from 1974 (n = 352, 0.2% of total output) was accidentally excluded during data collection, and hence was not included in the subsequent analysis. In addition, this study has focused on entries contained in the WOS only, and it should be noted that the employment of other databases including PubMed and Scopus may have yielded slightly different results [14,15]. The aforementioned discussion notwithstanding, there are a number of important limitations associated with the h index.…”
Section: Discussionmentioning
confidence: 99%
“…Output from 1974 (n = 352, 0.2% of total output) was accidentally excluded during data collection, and hence was not included in the subsequent analysis. In addition, this study has focused on entries contained in the WOS only, and it should be noted that the employment of other databases including PubMed and Scopus may have yielded slightly different results [14,15]. The aforementioned discussion notwithstanding, there are a number of important limitations associated with the h index.…”
Section: Discussionmentioning
confidence: 99%
“…6 Furthermore, a recent study of 24 accredited residency programs in the United States showed that the median number of career publications of academic anesthesiologists was just 3, with assistant, associate, and full professors having 1, 13, and 46, respectively, although the range within each rank was large. 1 Similar but modestly higher numbers were reported for groups of pediatric anesthesiologists 3 and academic anesthesiologists 3 in Canada. None of these studies included a nonanesthesiologist control group, but similar analyses of radiation oncologists and faculty in neurosurgery and urology suggest anesthesiologists publish less often than do these other specialists.…”
Section: Discussionmentioning
confidence: 54%
“…[1][2][3] The h-index is determined mainly by how often a publication is cited and is defined as the number (h) of an investigator's publications that have been cited at least h times. 4 …”
Section: Methodsmentioning
confidence: 99%
“…Leadership positions have been shown to positively correlate with NIH funding in radiology, urology, neurosurgery, orthopedic surgery, ophthalmology and among anesthesiologists [17,[19][20][21][22]. Department Chairs and Research Directors are often considered to be among the highest academically ranked individuals in the department.…”
Section: Resultsmentioning
confidence: 99%